2011
DOI: 10.1161/hypertensionaha.111.169961
|View full text |Cite|
|
Sign up to set email alerts
|

Addition of Spironolactone in Patients With Resistant Arterial Hypertension (ASPIRANT)

Abstract: Abstract-There is currently limited data on which drug should be used to improve blood pressure (BP) control in patients with resistant hypertension. This study was designed to assess the effect of the addition of 25 mg of spironolactone on BP in patients with resistant arterial hypertension. Patients with office systolic BP Ͼ140 mm Hg or diastolic BP Ͼ90 mm Hg despite treatment with at least 3 antihypertensive drugs, including a diuretic, were enrolled in this double-blind, placebo-controlled, multicenter tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(53 citation statements)
references
References 34 publications
4
48
0
1
Order By: Relevance
“…As documented in recent reports, use of aldosterone antagonists may be beneficial at least in obese, especially black female, patients with RHT [17,26]. The use of such agents in the present study is low but similar or even higher than that documented in recent reports [7].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As documented in recent reports, use of aldosterone antagonists may be beneficial at least in obese, especially black female, patients with RHT [17,26]. The use of such agents in the present study is low but similar or even higher than that documented in recent reports [7].…”
Section: Discussionsupporting
confidence: 79%
“…The use of such agents in the present study is low but similar or even higher than that documented in recent reports [7]. Nevertheless, the BMI in our study was in the overweight range, thus below that demonstrated for spironolactone to be effective [26]. In addition, patients, especially those with renal insufficiency, may not tolerate aldosterone blockade due to hyperkalemia or independent of this.…”
Section: Discussionsupporting
confidence: 52%
“…The recent Addition of Spironolactone in Patients With Resistant Arterial Hypertension (ASPIRANT) clinical trial administrated 25 mg spironolactone, an anti-mineralocorticoid agent that inhibits aldosterone, to patients whose blood pressure was not controlled by three antihypertensive drugs, including a diuretic. Analysis of 111 patients indicated that spironolactone significantly decreased systolic blood pressure, though its effect was not prominent on respective diastolic blood pressure [61]. These studies suggest that spironolactone may be an effective alternative to treat elevated systolic blood pressure in patients with resistant hypertension.…”
Section: Resistant Hypertensionmentioning
confidence: 99%
“…Regarding non-selective MR antagonists, Oka et al reported the use of multiple antihypertensive drugs including spironolactone for a patient with malignant hypertension caused by primary aldosteronism (13). In patients with resistant arterial hypertension including chronic kidney disease (CKD), Vaclavik et al reported that the addition of spironolactone to their antihypertensive medications significantly lowered the systolic blood pressure (14). In the present patient, the independent efficacy of eplerenone could not be evaluated.…”
Section: Discussionmentioning
confidence: 80%